Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1108/1525383x200800003
|View full text |Cite
|
Sign up to set email alerts
|

Multinationality, R&D Intensity, and Firm Performance: Evidence from U.S. Manufacturing Firms

Abstract: We examine whether firms’ multinationality leads to better performance and what the role of R&D investment is in the multinationality performance linkage. Unlike the previous studies, we employ both accounting‐ and market‐based measures of firm performance for a large sample of U.S. manufacturing firms. Our results show that the empirical relation between multinationality and performance is not monotonic but varies with the phase of a firm’s multinationality, starting with a negative relation initially, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 42 publications
2
46
0
3
Order By: Relevance
“…Moreover, the regression results confirm several scholars' research on American listed companies [1].…”
Section: The Impact Of Randd Expenditure On the Market Value Of Listed supporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, the regression results confirm several scholars' research on American listed companies [1].…”
Section: The Impact Of Randd Expenditure On the Market Value Of Listed supporting
confidence: 85%
“…Lots of literatures confirmed that the R&D expenditure showed a positive correlation with the market value of listed companies [1]. However, some empirical evidence didn't support the positive correlation between them.…”
Section: The Randd Expenditure and Market Value Of Manufacturinglisted mentioning
confidence: 99%
“…Some researchers have uncovered a positive linear relationship between multinationality and performance (e.g., Kim and Lyn, 1986), some a negative linear one (e.g., Click and Harrison, 2000), and still others have found that some specifications showed no relationship whatsoever (e.g., Tallman and Li, 1996;Qian, 2002). In response to these inconclusive results, researchers have experimented with nonlinear relationships, but here again the results have been inconsistent and contradictory, with some finding a U-shaped relationship (e.g., Capar and Kotabe, 2003), others an inverted U-shaped relationship (e.g., Li and Qian, 2005) and a third group a sigmoid one (Contractor, Kundu, and Hsu, 2003;Lu and Beamish, 2004;Bae, Park, and Wang, 2008). In the words of Osegowitsch and Zalan (2005: 8), 'the only conclusive verdict that can be reached is that M/P results are truly inconclusive.…”
Section: Introductionmentioning
confidence: 88%
“…Second, a fi rm's operational risk is also increased in three significant ways with international operations. These are risks due to changing political situations in the host countries, fluctuations in currency exchange values (Bae and Jain, 2002), and managerial mistakes due to liability of foreignness (Hymer, 1976;Lu and Beamish, 2005).…”
Section: Literature Review and Development Of Hypotheses Literature Rmentioning
confidence: 99%